PENGEMBANGAN MEDIA PEMBELAJARAN TPACK PADA MATA PELAJARAN PERENCANAAN DAN PENGALAMATAN JARINGAN DI SMK NEGERI 1 SEDAYU - Qotrunnada, Dafa Zenita; Jati, Handaru; Marpanaji, Eko (Department of Electronics and Informatics Engineering Education, 2024)
This research aims to develop and assess the feasibility of a web-based learning media using the Technological Pedagogical Content Knowledge (TPACK) approach. The method employed in this study is Research and Development (R&D) using the ADDIE development model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. Data was collected using a questionnaire instrument in the form of assessments from subject material experts, media experts, and usability testing by the 11th-grade students in the Computer Network and Telecommunication Engineering program at SMK Negeri 1 Sedayu. The research results indicate that the developed web-based learning media is highly suitable as a supportive tool for the learning process, with material expert assessment at 93.3% in the